Fluororesin molded article and production method thereof

By employing a fluororesin composition with high melt viscosity and specific inorganic filler content, along with a hot press molding method, the challenges of maintaining shape and achieving low linear expansion in fluororesin molded bodies are addressed, resulting in a product with practical strength for sealing and sliding applications.

JP2025039761APending Publication Date: 2025-03-21STARLITE
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2025003459
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing fluororesin molded bodies with high melt viscosity, such as polytetrafluoroethylene, face challenges in maintaining shape and achieving a low linear expansion coefficient when filled with inorganic fillers, leading to difficulties in forming molded bodies with practical strength for sealing or sliding applications.

Method used

A fluororesin molded body is created using a fluororesin composition with a melt viscosity of 10 Pa·sec or higher, incorporating a particulate inorganic filler with a D50 particle diameter of 0.01 to 1 μm and a content of 40% to 70% by volume, along with a fibrous inorganic filler if necessary, and employing a hot press molding method to ensure proper adhesion and shape retention.

Benefits of technology

The resulting fluororesin molded body achieves a linear expansion coefficient of 30 ppm/K or less and possesses practically acceptable strength, making it suitable for applications as sealing or sliding materials in rotating equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039761000001
    Figure 2025039761000001
Patent Text Reader

Abstract

To provide a fluororesin molded article having a linear expansion coefficient of a specified value or less and strength acceptable for practical use, and a production method capable of producing such a fluororesin molded article easily.SOLUTION: Provided is a fluororesin molded article formed of a fluororesin composition comprising inorganic filler, where the fluororesin composition comprises as a matrix a fluororesin having a melt viscosity of 1010 Pa sec or more, the inorganic filler comprises particulate inorganic filler having a D50 particle diameter of 0.01-1 μm, the particulate inorganic filler is not coated with a silane coating and is included in an amount of 40 vol% or more and 70 vol% or less relative to the whole fluororesin composition, and a linear expansion coefficient of the fluororesin molded article at 25-200°C is 30 ppm (3.0×10-5) / K or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fluororesin molded article and a method for producing the same. [Background technology]

[0002] Conventionally, labyrinth seals are often used as shaft seals for metal rotating shafts of various rotating devices. A labyrinth seal is one of the seal structures for fluids that flow along the axial direction of a rotating shaft through a gap between the outer circumferential surface of a rotating shaft and a stationary part provided on the housing side facing this surface. For example, by providing fins on the stationary part side, uneven gaps are formed between the rotating shaft and the stationary part in multiple stages, and the leakage pressure is gradually reduced for each stage to reduce the leakage amount. If the rotating shaft and the stationary part that constitute the labyrinth seal are both made of metal, the metals will seize together when they come into contact with each other, causing damage to the rotating device. In order to avoid this, it has been considered to make the stationary part out of resin. For example, fluororesin is an example of such a resin. This is because fluororesin has excellent characteristics such as heat resistance, chemical resistance, non-stickiness, and sliding properties, and is widely used for various sealing materials, sliding materials, and other applications. However, when fluororesin is used as a sealing material for the metal rotating shaft of a rotating device, the thermal expansion coefficient of fluororesin is larger than that of common metals such as aluminum and steel, which are commonly used for rotating shafts. As a result, the gap between the rotating shaft and the sealing material becomes larger as the temperature rises, and fluids may become more likely to leak from this gap.

[0003] As an improvement measure, Patent Document 1 proposes a sealing material in which voids in a sealing material obtained by molding a fluororesin composition consisting of 10 to 60% by weight of fluororesin, 37 to 60% by weight of natural graphite powder, and 2 to 30% by weight of carbon fiber are impregnated with a thermosetting resin and cured to seal the voids. The invention described in Patent Document 1 claims that by impregnating with a thermosetting resin in this way, it is possible to prevent fluid from penetrating and leaking from voids that occur when a large amount of graphite or carbon fiber is added to a conventional fluororesin, and to suppress the expansion of the gap between the rotating shaft and the sealing member that still occurs even when expanded graphite and carbon fiber are added to a specified modified polytetrafluoroethylene.

[0004] In fluororesin compositions applied to circuit board materials rather than the above-mentioned applications of sealing members and sliding materials, in order to use fluororesins with low dielectric constants instead of conventional polyimide resins and the like, it has been proposed to use a specific filler in order to improve the high thermal expansion coefficient of the fluororesin (e.g., Patent Documents 2 to 4).

[0005] Patent Document 2 discloses a fluororesin composition containing a fluororesin exhibiting melt flowability and silica, the fluororesin having 25 or more carbonyl-containing functional groups per 106 main chain carbon atoms, the silica being spherical silica, and having a linear expansion coefficient of 100 ppm / ° C. or less. Such a fluororesin composition is said to have low dielectric constant, low linear expansion coefficient, and excellent adhesion, thereby making it possible to suppress warping of substrates and improve heat cycle resistance.

[0006] Patent Document 3 discloses a composition having a low dielectric constant and a low coefficient of thermal expansion, which is composed of A. a fluorinated polymer material; and B. a filler having an average particle size not larger than about 7 μm and selected from the group consisting of silica, quartz particles, hollow microspheres, and mixtures thereof, which does not contain a fibrous filler, and in which the amount of A is about 50 to about 90% by weight and the amount of B is about 50 to about 10% by weight, based on the total amount of A and B in the composition. Such a fluororesin composition is said to be suitable for providing a substrate containing vias therein obtained by laser drilling and / or mechanical drilling and / or punching.

[0007] Patent Document 4 discloses an electrical substrate material that contains a fluoropolymer material, a ceramic filler material having a low dielectric constant, low loss and low coefficient of thermal expansion, and 2% or less by weight of a fiber reinforcement material, the filler material being in an amount of at least about 55% by weight of the total substrate material, and the ceramic filler material being coated with a silane coating. It is said that such an electrical substrate material exhibits improved electrical performance compared to the prior art, and exhibits relatively high compliance and a low coefficient of thermal expansion that results in improved surface mounting and plated through hole reliability. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2010-156398 A [Patent Document 2] International Publication No. 2020 / 145133 [Patent Document 3] Japanese Patent Application Publication No. 6-88000 [Patent Document 4] Japanese Patent Publication No. 63-259907 Summary of the Invention [Problem to be solved by the invention]

[0009] However, according to the results of the inventor's investigation of the sealing material described in Patent Document 1, it was found that when a fluororesin having a high melt viscosity and no melt fluidity, such as polytetrafluoroethylene, is used as a matrix and an inorganic filler is highly filled, it is difficult for a preform obtained by preforming to maintain its shape. In other words, it was found that it is difficult to manufacture a molded body by the general free sintering method (corresponding to the free baking described in Patent Document 1) in which a preform obtained by preforming is heated and sintered to manufacture a molded body.

[0010] In addition, the composition for circuit boards described in Patent Document 2 uses a fluororesin that exhibits melt flowability and has adhesive properties as a matrix, so there is room for improvement if it is used as a sealing member or a sliding member. Even if the composition for circuit boards described in Patent Document 3 can be used for coating purposes, it is considered difficult to maintain the shape of the molded product as in Patent Document 1. The composition for circuit boards described in Patent Document 4 uses a ceramic filler coated with a silane coating as an inorganic filler, so voids originating from the silane coating are generated in the molded product when it is heated and melted during molding, and a molded product having a desired linear expansion coefficient may not be obtained.

[0011] As described above, in the case of a fluororesin having a high melt viscosity and not showing melt fluidity, such as polytetrafluoroethylene, it is actually difficult to uniformly disperse inorganic fillers at a high filling rate when heated and melted, compared with a fluororesin having a low melt viscosity. As a result, it is difficult to suppress the thermal expansion of the molded body. In addition, when inorganic fillers are highly filled into a fluororesin having a high melt viscosity, when molding is performed using a general free sintering method, which is more mass-producible as a molding method using such a fluororesin, it is difficult to form a molded body having a practically acceptable strength, for example, in a molded body used for a sealing material or a sliding material.

[0012] Therefore, an object of the present invention is to provide a fluororesin molded article having a linear expansion coefficient of a predetermined value or less and a strength that is acceptable for practical use, and to provide a method for easily producing such a fluororesin molded article. [Means for solving the problem]

[0013] The present inventors have conducted extensive research to solve the above-mentioned problems. As a result, they have found that by using a particulate inorganic filler with a predetermined particle size for a predetermined fluororesin matrix and employing a predetermined manufacturing method, it is possible to easily obtain a fluororesin molded article with a linear expansion coefficient of a predetermined value or less and a practically acceptable strength. The gist of the present invention is as follows.

[0014] (1) A fluororesin molded article made of a fluororesin composition containing an inorganic filler, the fluororesin composition having a melt viscosity of 10 10 a matrix of a fluororesin having a D50 particle size of 0.01 to 1 μm, the particulate inorganic filler is not coated with a silane coating and is included in the fluororesin composition at 40% by volume or more and 70% by volume or less of the entire fluororesin composition; and the linear expansion coefficient of the fluororesin molded article at 25° C. to 200° C. is 30 ppm (3.0×10 -5 ) / K or less, Shape. (2) The fluororesin molded article according to the above (1), wherein the fluororesin is polytetrafluoroethylene. (3) The fluororesin molded article according to the preceding item (1) or (2), wherein the inorganic filler comprises a fibrous inorganic filler, and the fibrous inorganic filler is contained in an amount of 10% by volume or more and 30% by volume or less based on the total volume of the fluororesin composition. (4) The fluororesin molded article according to item (3) above, wherein the fibrous inorganic filler contains short fibers of pitch-based carbon fibers. (5) The fluororesin molded article according to any one of the above (1) to (4), wherein the particulate inorganic filler contains fused silica. (6) The fluororesin molded product according to any one of the preceding items (1) to (5), wherein the fluororesin composition contains, in addition to the fluororesin that serves as a matrix, an adhesive fluorine-containing copolymer as an additive, and the adhesive fluorine-containing copolymer is contained in an amount of 5 vol % or more and 10 vol % or less based on the total volume of the fluororesin composition. (7) The method for producing a fluororesin molded article according to any one of the above (1) to (6), further comprising hot-press molding in which the fluororesin composition is pressurized in a molten state and cooled and solidified under pressure. Effect of the Invention

[0015] According to the present invention, it is possible to provide a fluororesin molded article having a linear expansion coefficient of a predetermined value or less and a strength that is practically acceptable, and also to provide a method for easily producing such a fluororesin molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The fluororesin molded article according to the embodiment of the present invention is made of a fluororesin composition containing an inorganic filler. 10 The matrix is ​​a fluororesin having a viscosity of 30 Pa·sec or more. The inorganic filler contains a particulate inorganic filler having a D50 particle size of 0.01 to 1 μm. This particulate inorganic filler is preferably not coated with a silane coating. The particulate inorganic filler is contained in an amount of 40 volume % to 70 volume % of the entire fluororesin composition. This content is maintained in the fluororesin molded product. Furthermore, the linear expansion coefficient of this fluororesin molded product at 25°C to 200°C is 30 ppm (3.0 x 10 -5 ) / K or less. The volume % used as the content of a component contained in the fluororesin composition can be calculated, for example, from the density of the component used and the amount added.

[0017] By using particulate inorganic fillers with a specific fine particle size, 10Even if a fluororesin with a high melt viscosity of Pa·sec or more is used, and even if a particulate inorganic filler is filled at a high content in the fluororesin matrix during melt molding, the contact area between the fluororesin and the particulate inorganic filler in the fluororesin molded body increases, and the physical constraint of the fluororesin during thermal expansion increases, making it possible to keep the linear expansion coefficient at a predetermined value or less and imparting a practically acceptable strength to the fluororesin molded body. In addition, it is preferable that the particulate inorganic filler is not coated with a silane coating, which can suppress the generation of voids due to gas derived from the silane coating during melt molding. From this perspective, it is also possible to impart a low linear expansion coefficient and a practically acceptable strength to the fluororesin molded body.

[0018] The fluororesin that constitutes the matrix has a melt viscosity of 10 10 A fluororesin having a viscosity of Pa·sec or more is used. Examples of such fluororesins include polytetrafluoroethylene (PTFE), and PTFE is particularly preferred because it generally has excellent sliding properties, chemical resistance, and the like, and does not seize even when in contact at high speed. Since PTFE has such properties, it is suitable as a constituent material for, for example, a seal member for a metal rotating shaft of a rotating device. In particular, it is suitable as a matrix resin material for constituting a labyrinth seal for a metal rotating shaft. PTFE obtained by a known manufacturing method can be used, and examples thereof include fine powder (emulsion polymerization product) produced by emulsion polymerization and molding powder (suspension polymerization product) produced by suspension polymerization.

[0019] Melt viscosity is 10 10The content of the fluororesin having a viscosity of Pa·sec or more in the entire fluororesin composition can be, for example, 10 to 60% by volume, taking into consideration other components. By setting the content of the fluororesin within this range, a fluororesin composition molded product having better strength and a lower linear expansion coefficient can be obtained. The lower limit is preferably 15% by volume or more, more preferably 20% by volume or more, and even more preferably 25% by volume or more. The upper limit is preferably 55% by volume or less, more preferably 45% by volume or less, and even more preferably 40% by volume or less.

[0020] The melt viscosity of the fluororesin constituting the matrix can be measured, for example, in accordance with ASTM D 1238 using a flow tester (manufactured by Shimadzu Corporation).

[0021] The inorganic filler includes a particulate inorganic filler having a D50 particle size of 0.01 to 1 μm. The particulate inorganic filler means an inorganic filler other than a fibrous one. Examples of particulate inorganic fillers include silica, graphite, mica, talc, glass spheres, metal particles, and ceramic spheres. Among these, silica is preferred from the viewpoint of lowering the linear expansion coefficient of the molded body and from the viewpoint of uniform dispersion in the fluororesin. Silica may be crystalline or non-crystalline, but since it is easy to obtain spherical particles as described later, amorphous silica is preferred, and fused silica is more preferred. The shape of the particulate inorganic filler is not particularly limited, but a spherical shape is preferred from the viewpoints of uniform dispersion in the fluororesin matrix, high filling property, isotropy of thermal expansion of the molded body, and the like. The spherical shape is preferably close to a true sphere. As a standard for a true sphere, for example, the sphericity described in Patent Document 2 can be adopted. Specifically, a photograph is taken using a scanning electron microscope (SEM), and from the area and perimeter of the observed particles, the sphericity is calculated as follows: (sphericity) = {4π × (area) ÷ (perimeter) 2}. The closer the sphericity is to 1, the closer it is to a true sphere. The area and perimeter values ​​used to calculate the sphericity can be average values ​​measured for 100 particles using an image processing device, for example. The sphericity calculated in this manner is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, and most preferably 0.95 or more. As described above, spherical fused silica is particularly suitable as a particulate inorganic filler having a predetermined particle size. Such spherical fused silica can be commercially available.

[0022] The particulate inorganic filler is preferably not coated with a silane coating as described in Patent Document 4. As described above, this can suppress the generation of voids due to gas derived from the silane coating during melt molding using a fluororesin composition. This effectively reduces the linear expansion coefficient due to the particulate inorganic filler. As described above, the significance of not being coated with a silane coating is to prevent the generation of gas derived from the coating during melt molding. Therefore, it is preferable to use a filler that is not coated with a silane coating but does not contain a coating containing a component that causes the generation of such gas. Conversely, a coating may be formed as long as it does not contain a substance that causes gas. In addition, there are cases where the particulate inorganic filler is acceptable even if it is coated with a silane coating.

[0023] The particle size of the particulate inorganic filler may be within the above-mentioned range of D50 particle size (median size). The content of such particulate inorganic filler may be within the above-mentioned range of the entire fluororesin composition. The D50 particle size of the particulate inorganic filler may be measured, for example, by a laser diffraction / scattering method.

[0024] The inorganic filler may contain a fibrous inorganic filler from the viewpoint of improving the strength of the molded body and from the viewpoint of sliding properties. Examples of the fibrous inorganic filler include carbon fiber, glass fiber, metal fiber, whisker, etc., but carbon fiber is preferred from the viewpoint of uniform dispersion in the fluororesin matrix, since it has a specific gravity close to that of the matrix fluororesin. The type of carbon fiber is not particularly limited, and may be pitch-based or PAN-based, but pitch-based carbon fibers are preferred from the viewpoint of further improving the sliding properties. The size of the carbon fiber is not particularly limited, but short fibers with an average fiber length of 0.1 to 0.3 mm and an average fiber diameter of 5 to 20 μm are preferred from the viewpoint of uniform dispersion. As described above, short fibers of pitch-based carbon fibers are particularly preferred as the fibrous inorganic filler.

[0025] From the viewpoint of uniform dispersion in the fluororesin matrix, the inorganic filler preferably has a specific gravity close to that of the fluororesin matrix. In other words, the specific gravity of the particulate inorganic filler and fibrous inorganic filler is preferably close to that of the fluororesin, and the ratio of the specific gravities is preferably 0.7 to 1.5.

[0026] The content of the particulate inorganic filler is 40% by volume or more and 70% by volume or less with respect to the entire fluororesin composition. When a fibrous inorganic filler is contained, the content is preferably 10% by volume or more and 30% by volume or less with respect to the entire fluororesin composition from the viewpoint of the strength of the molded body. In addition, the content of the inorganic filler is preferably 80% by volume or less with respect to the entire fluororesin composition. In other words, when a particulate inorganic filler and a fibrous inorganic filler are contained, the total of both is preferably 80% by volume or less. From the viewpoint of the linear expansion coefficient and strength of the molded body, the content of the inorganic filler is preferably 40% by volume or more, more preferably 50% by volume or more. When a particulate inorganic filler and a fibrous inorganic filler are contained, the total of both is preferably 50% by volume or more.

[0027] In addition to the above-mentioned components, the fluororesin composition may contain an adhesive fluorine-containing copolymer as an additive, particularly a dispersing aid, from the viewpoint of improving the dispersibility of the inorganic filler in the matrix of a specific fluorine resin. Examples of the adhesive fluorine-containing copolymer include fluorine-containing copolymers having adhesive functional groups introduced into the main chain skeleton. Examples of the fluorine-containing copolymers constituting the main chain skeleton include tetrafluoroethylene-perfluoroalkyl vinyl ether copolymers (PFA), copolymers having chlorotrifluoroethylene (CTFE) units (CTFE copolymers), tetrafluoroethylene-hexafluoropropylene copolymers (FEP), tetrafluoroethylene-ethylene copolymers (ETFE), polychlorotrifluoroethylene (PCTFE), chlorotrifluoroethylene-ethylene copolymers (ECTFE), polyvinylidene fluoride (PVDF), and polyvinyl fluoride (PVF), tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymers (THV), and tetrafluoroethylene-vinylidene fluoride copolymers. In addition, examples of the adhesive functional groups that can be introduced into such fluorine-containing copolymers include carbonyl-containing functional groups. Examples of the carbonyl-containing functional groups include carbonate groups, carboxylic acid halide groups (halogenoformyl groups), formyl groups, carboxyl groups, ester groups [-C(=O)O-], acid anhydride groups [-C(=O)OC(=O)-], isocyanate groups, amide groups, imide groups [-C(=O)-NH-C(=O)-], urethane groups [-NH-C(=O)O-], carbamoyl groups [NH2-C(=O)-], carbamoyloxy groups [NH2-C(=O)O-], ureido groups [NH2-C(=O)-NH-], and oxamoyl groups [NH2-C(=O)-C(=O)-] that are part of the chemical structure. Examples of such adhesive fluorine-containing copolymers include those described in Patent Document 1, and PFAs (also called adhesive PFAs) having adhesive functional groups introduced therein described in Japanese Patent No. 4424246, Japanese Patent No. 5365939, and Japanese Patent No. 5263269. Among these, adhesive PFAs are preferred. Commercially available adhesive PFAs can be used.

[0028] The content of the adhesive fluorine-containing copolymer is preferably 5 to 10% by volume based on the total volume of the fluororesin composition. The ratio (A / B, by volume) of the adhesive fluorine-containing copolymer (B) to the fluororesin (A) serving as the matrix is ​​preferably 3 / 1 to 8 / 1.

[0029] The fluororesin composition may contain other additives in addition to the above-mentioned components. Examples of such additives include colorants. The content of such additives may be 5% by volume or less.

[0030] The fluororesin composition can be obtained by mixing the above-mentioned components to a desired volumetric content and stirring with a stirrer such as a Henschel mixer. The properties of the fluororesin composition are appropriately determined depending on the properties of each component and the conditions during mixing, but it is preferable that the fluororesin composition is in a powder form from the viewpoint of ensuring a good mixing state of each component and the viewpoint of uniform dispersion of each component during melt molding. When obtaining such a powdered fluororesin composition, it is preferable to use each component in a powder form, and it is preferable to adjust the temperature so that each component can be maintained in a powder form during stirring. In addition, it is preferable to use each component in a powder form with a similar specific gravity. The content of each component can be calculated from the mass of each component added and the density of each component as described above. In addition, the volumetric content of each component in the fluororesin composition is maintained in the molded product.

[0031] The fluororesin molded article according to the embodiment is, for example, a molded article made by using the above-mentioned fluororesin composition. By producing the molded article by the method described below, for example, the molded article can have a linear expansion coefficient of a predetermined value or less. The molded article has a practically acceptable strength for use in applications such as sealing materials and sliding materials. The linear expansion coefficient can be measured by a method conforming to JIS K7197. The standard for practically acceptable strength can be, for example, a 5% compressive strength of 10 MPa or more when the compressive strength (compression speed 5 mm / min) is measured by JIS K7181, as described below.

[0032] The fluororesin molded article can be produced, for example, by hot press molding, which is characterized in that the above-mentioned fluororesin composition is pressurized in a molten state and then cooled and solidified under pressure as described below. First, the desired fluororesin composition is filled into, for example, a compression molding die, and compressed at room temperature at a predetermined pressure for a predetermined time using a compression press, and then the pressure is released (premolding process). In the free sintering method, the premolded product is then released from the mold and placed in a heating furnace, but when the above-mentioned fluororesin composition is used, it is difficult or impossible to maintain the shape. Therefore, it has been found that the following process can finally maintain the shape and provide the desired linear expansion coefficient and strength.

[0033] After the preforming step, the compression molding die filled with the fluororesin composition and depressurized is placed in a heating furnace heated to a temperature equal to or higher than the melting point of the fluororesin, and heated for a predetermined period of time to melt the fluororesin in the compression die (in-mold heating and melting step). Any heating furnace can be used as long as it can uniformly heat the die, and for example, a hot air circulation furnace can be used.

[0034] Next, the compression molding die is taken out of the heating furnace while the fluororesin is still in a molten state, and immediately placed in a compression press, and pressure is started at room temperature at a pressure equal to or greater than the pressure during the preforming process. After the die temperature reaches 150°C or less, the pressure is released and the die is demolded (compression molding process). After cooling to room temperature, it can be machined into a desired shape as necessary. In this way, it is believed that the fluororesin in a molten state is cooled and solidified under pressure, and the fluororesin sufficiently wets the inorganic filler, increasing the interfacial adhesion between the fluororesin particles and the inorganic filler, resulting in a molded product that has practically acceptable strength and can maintain its shape. When the fluororesin is PTFE, it is believed that the desired molded product can be obtained by good fusion between the PTFE particles.

[0035] The above-mentioned fluororesin molded article has a low linear expansion coefficient of a predetermined value or less, and thus can suppress dimensional changes due to heating, and can be applied to various applications in which it is used in combination with a member having a low linear expansion coefficient. In particular, since it contains a predetermined fluororesin as a matrix, it is suitable as a seal member or a sliding material for various rotating devices. In particular, it is suitable as a seal member for a metal rotating shaft of a rotating device, and in particular as a seal member constituting a labyrinth seal or an abradable seal. An abradable seal is a seal having a seal member to be cut in a stationary part, and the seal member to be cut is cut by the rotation of a fin formed on the rotating shaft, thereby ensuring an optimal distance. A labyrinth seal is one that does not use a seal member to be cut such as an abradable seal, and as described above, for example, a fin is provided on the stationary part side, and uneven gaps are formed between the rotating shaft and the stationary part in multiple stages. The above-mentioned labyrinth seal of a rotating device is particularly suitable as a seal member for a turbo compressor. EXAMPLES

[0036] Hereinafter, the embodiment of the present invention will be described in more detail based on examples.

[0037] Example 1 <Preparation of Fluororesin Composition> PTFE (fine) (manufactured by Mitsui-Chemours Fluoro Products Co., Ltd., Teflon (registered trademark) PTFE fine powder 641-J, emulsion polymerization product, average particle size: 400 μm, specific gravity: 2.17, melting point: 327°C, melt viscosity: 10 12 Pa·sec) 35% by volume, particulate inorganic filler (Denka Co., Ltd., UFP-35HH, fused silica, D50 particle size: 0.1 μm, specific gravity: 2.2, shape: spherical (spherical)) 40% by volume, fibrous inorganic filler (Kureha Co., Ltd., Kreka Chop KGF-200 M-201S, carbon fiber, pitch-based, average fiber length 0.15 mm, average fiber diameter 14.5 μm, specific gravity: 1.60) 20% by volume, adhesive fluorine-containing copolymer (AGC Co., Ltd., Fluon+ EA-2000 powder, specific gravity: 2.13, melting point: 310°C, melt viscosity: 10 4The mixture was mixed with 5% by volume of PFA (Pa·sec, adhesive functional group-introduced PFA) and stirred for 2 minutes in a small laboratory blender to obtain a fluororesin composition.

[0038] <Production of fluororesin molded products> The obtained fluororesin composition was used to obtain a fluororesin molded product by hot press molding as follows. First, the obtained fluororesin composition was put into a compression molding die capable of forming a cylindrical space of φ40 mm, and premolded in a compression press at a molding pressure of 10 MPa and a die temperature of 25°C. Then, the die with the composition in it was heated in a heating furnace at 360°C to melt the PTFE. Next, the die was removed from the heating furnace and placed in a compression press so that the PTFE remained in a molten state, and naturally cooled while being pressurized at 30 MPa, and then demolded to obtain a fluororesin molded product of φ40 mm x 70 mm in height. The obtained fluororesin molded product was used for the evaluation described below.

[0039] Example 2 PTFE (fine) was replaced with PTFE (molding) (manufactured by Mitsui-Chemours Fluoro Products Co., Ltd., Teflon (registered trademark) PTFE molding powder 7-J, suspension polymerization product, average particle size 30 μm, specific gravity 2.17, melting point: 327°C, melt viscosity: 10 12 A fluororesin composition was prepared and a fluororesin molded article was produced in the same manner as in Example 1, except that the viscosity was changed to 100 Pa·sec. The obtained fluororesin molded article was used for the evaluations described below.

[0040] Example 3 A fluororesin composition was prepared and a fluororesin molded article was produced in the same manner as in Example 1, except that the PTFE content was set to the content shown in Table 1, and SFP-30M (fused silica, D50 particle size: 0.7 μm, specific gravity: 2.2, shape: spherical (spherical shape)) manufactured by Denka Co., Ltd. was used as the particulate inorganic filler at the content shown in Table 1. The obtained fluororesin molded article was used for the evaluation described later.

[0041] (Examples 4 and 5, Comparative Examples 1 to 3) A fluororesin composition was prepared and a fluororesin molded article was produced in the same manner as in Example 1, except that the component composition was as shown in Table 1. The obtained fluororesin molded article was used for the evaluations described below. In Comparative Example 2, mica (manufactured by Yamaguchi Mica Co., Ltd., SJ-005, D50 particle size: 5 μm) was used as the particulate inorganic filler.

[0042] (Reference example 1) A fluororesin composition was prepared in the same manner as in Example 1, except that the component composition was as shown in Table 1. Using this fluororesin composition, an attempt was made to manufacture a fluororesin molded body by the free sinter molding method as described below. First, the obtained fluororesin composition was placed in a compression molding die capable of forming a cylindrical space of φ40 mm, and premolded by a compression press at a molding pressure of 50 MPa and a die temperature of 25°C. After that, when it was released from the die, the premolded body was very brittle and could not retain its shape, and could not be heated and sintered. In other words, a molded body could not be obtained by the free sinter method.

[0043] (evaluation) <Measurement of linear expansion coefficient> The linear expansion coefficient was measured according to JIS K7197. First, test pieces of φ5×10 mm were prepared by machining from the fluororesin molded articles obtained in Examples 1 to 5 and Comparative Examples 1 to 3. Next, the average linear expansion coefficient was measured for each of the obtained test pieces by increasing the temperature at 5° C. / min in the temperature range of 25° C. to 200° C. using a thermomechanical measuring device (TMA / SS6100, manufactured by Hitachi High-Tech Science Corporation). The evaluation results are shown in Table 1.

[0044] <Compressive strength measurement> Compressive properties were measured in accordance with JIS K7181. First, test pieces of φ8×20 mm were prepared by machining from the fluororesin molded articles obtained in Examples 1 to 5 and Comparative Examples 1 to 3. Next, the compressive strength of each of the obtained test pieces was measured at a test speed of 5 mm / min using an autograph AG-X plus manufactured by Shimadzu Corporation, and the 5% compressive strength was calculated. The evaluation results are shown in Table 1.

[0045] Table 1 shows the component compositions, molding methods, moldability, and evaluation results of Examples 1 to 5, Comparative Examples 1 to 3, and Reference Example 1. The item "Moldability" in Table 1 indicates whether molding was possible using each molding method employed, with "◯" indicating that a molded body was produced without any problems and "×" indicating that a preform could not be formed.

[0046] [Table 1]

[0047] As shown in Table 1, in the case of the fluororesin compositions (Examples 1 to 5) that have a fluororesin with a predetermined melt viscosity as a matrix and contain a specific particulate inorganic filler at a predetermined content, the fluororesin molded articles obtained by hot press molding have a predetermined linear expansion coefficient and a deformation strength that is practically acceptable.

Claims

1. A fluororesin molded article made of a fluororesin composition containing an inorganic filler, The fluororesin composition has a melt viscosity of 10 10 A fluororesin having a viscosity of Pa·sec or more is used as a matrix, The inorganic filler comprises a particulate inorganic filler having a D50 particle size of 0.01 to 1 μm, the particulate inorganic filler is not coated with a silane coating, and is included in the fluororesin composition in an amount of 40% by volume or more and 70% by volume or less based on the entire fluororesin composition; The linear expansion coefficient of the fluororesin molded article at 25° C. to 200° C. is 30 ppm (3.0×10 -5 ) / K or less.

2. 2. The fluororesin molded article according to claim 1, wherein the fluororesin is polytetrafluoroethylene.

3. 3. The fluororesin molded article according to claim 1, wherein the inorganic filler comprises a fibrous inorganic filler, and the fibrous inorganic filler is contained in an amount of 10% by volume or more and 30% by volume or less based on the entire fluororesin composition.

4. 4. The fluororesin molded article according to claim 3, wherein the fibrous inorganic filler contains short fibers of pitch-based carbon fibers.

5. 3. The fluororesin molded article according to claim 1, wherein the particulate inorganic filler contains fused silica.

6. The fluororesin composition contains an adhesive fluorine-containing copolymer as an additive in addition to the fluororesin that serves as a matrix, 3. The fluororesin molded article according to claim 1, wherein the adhesive fluorine-containing copolymer is contained in an amount of 5% by volume to 10% by volume based on the total volume of the fluororesin composition.

7. The method for producing a fluororesin molded article according to claim 1 or 2, further comprising hot-press molding in which the fluororesin composition in a molten state is pressurized and cooled and solidified under pressure.

Citation Information

Patent Citations

  • Composite material for electrical use, laminated sheet and printed wiring board

    JP1991212987A

  • Resin composite composition and method for production of the same

    JP2007119769A

  • Composite materials and method of manufacturing the same

    KR1020180099178A

  • Electric base body material

    JP1988259907A

  • Fluoropolymer composition and its production

    JP1994088000A